Model Simulasi Pertumbuhan dan Produksi Tanaman Tebu - Pembengo, Wawan; ., Suwarto (Jurnal Agroteknotropika, 2012)
To reduce the level of difficulty conducting research in complex systems, modeling is defined as simplification of system with mechanistic approach, can be an alternative approach for understanding and prediction ecophysiology process of growth, development and production plants. Modeling the growth of sugarcane crop is expected to be used as a tool to predict the production of sugarcane production as well as in a development area. Research purposes that make simulation model of sugarcane growth and development develop the tools in an effort to plan and optimize the productivity of sugarcane and sugar productivity predicts. The experiment was conducted in Kotabumi of Lampung regency. Began in June 2008 ended in July 2009. Research materials in the form of climate data for 2 years (2008 to 2009), soil data, the data accumulation, and agronomic data. Tool in this study the precipitation gauge type observatory, TL-1 Illuminance meter to measure the radiation coming, belgi drill, sample ring, digital scales and oven. Research using analytical methods or simulation models of plant systems are supported field trials. The model is built based on the variables and parameters obtained from secondary data as well as from experiments. Construction of a simulation model of sugarcane growth and development has been able to simulate and describe the development and growth of sugarcane as shown by the results of field observations. The simulation results for the production of sugarcane harvested biomass 100 ton/ha while the observation of 85 ton/ha (the simulation results have to be in the range of values one standard deviation from the average). Phenological period and the prediction accuracy of the simulation results are relatively consistent with the observation field (simulated total biomass production 115 ton/ha while the observation of 101 ton/ha).